The Ethnomathematics of Chinese Tulou Building Architecture as Geometry Teaching Material in Elementary School - Huang, Yuxian; Nong, Jinyu; Lai, PeiPei (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
The purpose of this study is to study ethnomathematics aspects contained in Chinese Tulou architecture. The study uses the qualitative research method to describe the ethnomathematics value of Tulou building in China, and then connect Chinese Tulou building with mathematics. The method of data collection is document's content analysis. The study found that Chinese Tulou contains a wealth of mathematical knowledge, including mathematical knowledge of geometric figures in mathematics, such as circle, triangle, rectangle, square, octagon, cylinder, octaprism, as well as the area and volume of geometric figures. Therefore, in daily teaching life, teachers can use Tulou as teaching materials, which was not only help students understand mathematics knowledge but also improve the enthusiasm of students.